THE ROLE OF THE ENGLISH SUBJECT TEACHERS CONFERENCE (MGMP) IN IMPROVING THE PROFESSIONAL COMPETENCE OF SENIOR HIGH SCHOOL TEACHERS IN PEMALANG REGENCY - Mustaidah, Mustaidah; Wuryandini, Endang; Muhtarom, Muhtarom (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2026)
This research aims to analyze and identify the contributory role of the English Subject Teachers’ Deliberative Group (Musyawarah Guru Mata Pelajaran - MGMP) in enhancing the professional competence of Senior High School (SMA) English teachers in Pemalang Regency. The study employed a qualitative approach with a case study method to deeply explore the implementation and impact of MGMP English activities. Data collection utilized triangulation techniques, including in-depth interviews, participant observation, and documentation analysis. The study concludes that MGMP English significantly contributes to the enhancement of teachers' professional competence through the implementation of various structured programs, such as training and workshops, focused group discussions, and collaborative learning. Active teacher involvement in MGMP activities was proven to improve their skills in developing English Lesson Plans (RPP), implementing innovative learning methods, and effectively conducting student learning outcome evaluations. Nevertheless, challenges were identified, including limited time, resources, and sub-optimal institutional support. This study provides important insights into the vital role of MGMP English in improving the quality and professionalism of SMA teachers, particularly in the field of language teaching, within Pemalang Regency.